Human stem cell–derived monocytes and microglia‐like cells reveal impaired amyloid plaque clearance upon heterozygous or homozygous loss of TREM2. Issue 3 (12th November 2018) - Claes, Christel; Van Den Daele, Johanna; Boon, Ruben; Schouteden, Sarah; Colombo, Alessio; Monasor, Laura Sebastian; Fiers, Mark; Ordovás, Laura; Nami, FatemehArefeh; Bohrmann, Bernd; Tahirovic, Sabina; De Strooper, Bart; et al.
Abstract: Introduction: Murine microglia expressing the Alzheimer's disease–linked TREM2 R47H mutation display variable decrease in phagocytosis, while impaired phagocytosis is reported following loss of TREM2. However, no data exist on TREM2 +/R47H human microglia. Therefore, we created human pluripotent stem cell (hPSC) monocytes and transdifferentiated microglia‐like cells (tMGs) to examine the effect of the TREM2 +/R47H mutation and loss of TREM2 on phagocytosis. Methods: We generated isogenic TREM2 +/R47H, TREM2 +/−, and TREM2 −/− hPSCs using CRISPR/Cas9. Following differentiation to monocytes and tMGs, we studied the uptake of Escherichia coli fragments and analyzed amyloid plaque clearance from cryosections of APP/PS1 +/− mouse brains. Results: We demonstrated that tMGs resemble cultured human microglia. TREM2 +/− and TREM2 −/− hPSC monocytes and tMGs phagocytosed significantly less E. coli fragments and cleared less amyloid plaques than wild‐type hPSC progeny, with no difference for TREM2 +/R47H progeny. Discussion: In vitro phagocytosis of hPSC monocytes and tMGs was not affected by the TREM2 +/R47H mutation but was significantly impaired in TREM2 +/− and TREM2 −/− progeny.